Evaluation of therapeutic effectiveness of prescribed medications in patients with type 2 diabetes mellitus: Findings from a tertiary care hospital, Lahore, Pakistan - Bareera Rana; Allah Bukhsh; Tahir Mehmood Khan; Ammar Sarwar; Muhammad Ovais Omer; Shazia Qasim Jamshed (Wolters Kluwer Medknow Publications, 2017)
Aim: The present study was aimed to highlight the current prescribing pattern of oral hypoglycemia in type 2 diabetes mellitus and to evaluate the therapeutic effectiveness of these therapeutic categories in achieving target glycemic control. Methods: This is a prospective, cross-sectional, observational study of 6 months' duration conducted in a tertiary care hospital of Lahore, Pakistan. Results: The current research recruited 145 patients presented in diabetes management center of a tertiary care hospital in Lahore, Pakistan. Mean age of the participants was 50.2 (± 8.5) years. Out of the 145 patients, 63% were females and 37% were males. Most patients were diagnosed to have diabetes within the past 5 years. Diabetes-induced neuropathy was the most common complication (71.7%) among the patients. A large proportion of these patients (70.3%) were also suffering from other comorbidities among which the most common one is hypertension. The average number of prescribed medications was 1.31. Metformin was prescribed to a majority of patients (64%) as monotherapy while 28.96% received combination therapy. Mean glycated hemoglobin (HBA1c) before and after 3 months of treatment was 8.5 (± 2.3) and 8.04 (± 2.1), respectively. Inferential statistics show a strong association between HBA1c and life style modifications and adherence to medication therapy (P = 0.05). However, the correlation between HBA1c and Morisky score and duration of disease was inverse and weak (P = 0.6, 0.4). The t-test values show a small difference between HBA1c values before and after 3 months (t = 0.440 and 0.466, respectively). Conclusion: Optimization of medication regimen and continuous patient education regarding life style modification and adherence to medication therapy are necessitated to bring HBA1c values near to target.